A heat-insulating glove based on phase change heat storage
By designing flexible thermally conductive phase change layer and phase change thermal storage aerogel in phase change thermal insulation gloves, combined with specific materials, the problems of poor flame retardant performance, self-healing ability and flexible performance of existing gloves are solved, achieving multiple performance improvements and significant improvements in user experience.
Patent Information
- Application Number
- CN202411130120.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-08-16
AI Technical Summary
The flame retardant performance, self-healing ability and flexibility of existing phase change heat storage gloves are poor, making it difficult to meet the needs of high-performance heating gloves.
A thermal insulation glove based on phase change heat storage is designed, using a flexible thermally conductive phase change layer and a phase change heat storage aerogel, combined with PEG10000, isophorone diisocyanate, tetrabromobisphenol A and micro-nano boron nitride filler to achieve multiple performance improvements.
It significantly improves the comprehensive performance of heating gloves, including excellent phase change heat storage, flame retardant performance, self-repair performance, mechanical properties and thermal conductivity, extending the service life of the gloves and improving the user experience.
Smart Images

Figure CN118986017B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electric heating gloves, and in particular to a pair of heat-insulating gloves based on phase change heat storage. Background Art
[0002] With the advancement of science and technology and the improvement of living standards, people's demand for personal protective equipment continues to grow. When working in a cold environment or doing outdoor activities, it is essential to keep your hands warm and flexible. Although traditional electric heating gloves can provide continuous heat, they rely on power supply. Once the power is cut off or exhausted, they can no longer continue to play the warming function. Phase change heat storage insulation gloves introduce phase change materials into gloves, and use their high phase change enthalpy characteristics to absorb or release a large amount of latent heat when the ambient temperature changes, thereby achieving a long-lasting insulation effect. Therefore, it is of great significance to develop phase change heat storage insulation gloves with long-lasting insulation effect.
[0003] At present, phase change heat storage gloves have made a lot of progress, but there are still some shortcomings. (1) Flame retardant performance still needs to be further improved to meet more stringent use environment requirements. For example, the Chinese patent with publication number CN206260906U discloses a heating glove. In the design scheme, an electric heating coil and a phase change material are provided between the inner layer and the outer layer. Although the specific phase change heat storage material is not disclosed, if a flammable material with a low flash point is used as a phase change material, such as paraffin, fatty acid, etc., as a phase change heat storage material, once the electric heating coil is short-circuited, the phase change heat storage material is bound to cause safety hazards. (2) Self-healing ability. The current design of phase change heat storage materials in gloves has almost no consideration of self-healing ability, which affects the service life of the gloves to a certain extent. (3) Poor flexibility. Phase change materials are usually in the form of powder or microcapsules in heating gloves, which inevitably has the problem of poor flexibility. For example, the Chinese patent with publication number CN202873889U discloses a heat-insulating glove based on a powdered phase change heat storage material. Therefore, the powdered phase change heat storage material has the problem of poor flexibility. In order to further improve the performance of the current phase change heat storage gloves, it is necessary to develop a new type of heating gloves so that the phase change heat storage material of the heating gloves has excellent flame retardant properties, self-healing and flexibility properties, etc., to meet the needs of high-performance heating gloves. Summary of the invention
[0004] (1) Technical issues solved
[0005] The purpose of the present invention is to provide a phase change heat storage thermal insulation glove to solve the problem that the current phase change heat storage material has poor performance such as flame retardancy, self-healing and flexibility.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A heat-insulating glove based on phase change heat storage comprises a glove body, which comprises an outer layer, a phase change heat storage aerogel, a heating layer, a flexible heat-conducting phase change layer and an inner layer from the outside to the inside; the outer layer, the phase change heat storage aerogel, the heating layer, the flexible heat-conducting phase change layer and the inner layer are connected together by stitches and a silicone adhesive; a power storage bag is provided at the cuff on the surface of the glove body; the power storage bag is made of leather fabric; a zipper is provided on the surface of the power storage bag for easy access; a rechargeable power supply is provided inside the power storage bag; a temperature control module is also provided on the back of the glove body; the temperature control module is provided with a temperature control button; the rechargeable power supply and the heating layer are respectively connected to the temperature control module through wires.
[0009] Furthermore, the preparation method of the flexible thermally conductive phase change layer is as follows: by weight, 25 to 45 parts of PEG10000, 5 to 12 parts of isophorone diisocyanate and 3 to 8 parts of micro-nano boron nitride filler are dissolved in 60 to 90 parts of chloroform, then heated to 60 to 70°C and stirred for 2 to 4 hours, then 1 to 4 parts of tetrabromobisphenol A and 0.3 to 0.8 parts of dibutyltin dilaurate catalyst are added and stirred for 2 to 4 hours to obtain a prepolymer mixed solution, then 1 to 3 parts of triethanolamine and 3 to 8 parts of chloroform are mixed, and then the mixed solution is added to the prepolymer mixed solution, stirred for 4 to 10 minutes, and then the solution is introduced into a tetrafluoroethylene mold, and then scraped evenly with a knife, and then the solution in the mold is heated and dried in an oven at 70 to 85°C for 10 to 18 hours to finally obtain a flexible thermally conductive phase change layer.
[0010] Furthermore, the preparation method of the phase change heat storage aerogel is as follows: in parts by weight, 3 to 7 parts of styrene-ethylene-butadiene-styrene block copolymer, 10 to 16 parts of eicosane, and 30 to 45 parts of tetrahydrofuran are stirred at room temperature for 2 to 5 hours, and then 20 to 35 parts of Kevlar fiber aerogel are completely impregnated therein, and then dried in a vacuum drying oven at room temperature for 24 to 36 hours to obtain the phase change heat storage aerogel.
[0011] Furthermore, the preparation method of the micro-nano boron nitride filler is as follows: by weight, 20 to 35 parts of a boron nitride whisker preform, 3 to 6 parts of a borane ammonia complex, 0.3 to 0.8 parts of ferrocene and 10 to 18 parts of dimethylformamide are mixed at room temperature and stirred for 20 to 25 minutes, and then dried completely in a vacuum drying oven, and then placed in a tubular furnace at 1000 to 1200° C., and heat treated for 2 to 4 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 5 to 10%, and after the reaction is completed, cooled to room temperature to obtain a micro-nano boron nitride filler.
[0012] Furthermore, the preparation method of the boron nitride whisker preform is as follows: by weight, 4 to 10 parts of boric acid, 5 to 12 parts of melamine and 100 parts of deionized water are magnetically stirred at 80 to 95° C. for 30 to 60 minutes, and then a white boron nitride precursor is obtained by freeze drying, which is then placed in a tubular furnace at 900 to 1100° C. and heat treated for 3 to 6 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 5 to 10%, and after the reaction is completed, the preform is cooled to room temperature to obtain a boron nitride whisker preform.
[0013] Furthermore, the micro-nano boron nitride filler is composed of micrometer-scale boron nitride whiskers and nanometer-scale boron nitride nanowires, wherein the boron nitride nanowires are uniformly dispersed on the surface of the boron nitride whiskers in a radial form.
[0014] The present invention adopts the design of a flexible thermally conductive phase change layer with the following multiple purposes: 1. In terms of phase change heat storage, the flexible thermally conductive phase change layer uses PEG10000 as a phase change material. PEG10000 has a high phase change heat storage point, which can absorb and store the heat of the thermal fluctuation of the glove heating layer to avoid scalding the hands. At the same time, it mainly plays its thermal conductivity function when the temperature is low. 2. In terms of flame retardancy, the introduction of tetrabromobisphenol A gives the layer good flame retardancy. 3. In terms of self-repair ability, the phenolic hydroxyl group in tetrabromobisphenol A can form a dynamic covalent bond with isocyanate, so that the layer has self-repair ability. 4. In terms of mechanical properties, the mechanical properties of the layer can be optimized by adjusting the ratio of PEG10000 to isophorone diisocyanate and tetrabromobisphenol A to obtain suitable tensile strength and elongation at break. 5. In terms of thermal conductivity, the preparation of micro-nano boron nitride filler uses raw materials such as boron nitride whisker preform, borane ammonia complex, ferrocene, etc., and is obtained by heat treatment at high temperature. Among them, the boron nitride whisker preform is prepared by reacting boric acid, melamine, etc. at high temperature. This micro-nano boron nitride filler has excellent thermal conductivity. It is composed of micron-scale boron nitride whiskers and nano-scale boron nitride nanowires. The boron nitride nanowires are evenly distributed on the surface of the boron nitride whiskers in a radial shape. This fine microstructure greatly improves the thermal conductivity efficiency of the filler, effectively improves the thermal conductivity of the entire flexible thermal conductive phase change layer, and can effectively improve the thermal conductivity of the flexible thermal conductive phase change layer. In summary, the present invention cleverly combines PEG10000, isophorone diisocyanate, tetrabromobisphenol A and micro-nano boron nitride fillers into a polyurethane network to prepare a multifunctional flexible thermal conductive phase change layer. This layer has excellent phase change heat storage performance, flame retardant performance, self-healing performance, mechanical properties and thermal conductivity, and has broad application prospects in heating gloves.
[0015] Furthermore, the preparation method of the Kevlar fiber aerogel is as follows: by weight, 5 to 10 parts of hydroxyapatite and 45 to 70 parts of dimethyl sulfoxide are mixed evenly to obtain a solution A for standby use; 20 to 35 parts of Kevlar fiber and 20 to 35 parts of potassium hydroxide are mixed evenly, and then added to 120 to 155 parts of dimethyl sulfoxide and stirred for 48 to 54 hours to obtain a reddish-brown colloid; then, the solution A is added to the reddish-brown colloid, and stirring is continued for 10 to 20 hours, and then the Kevlar fiber aerogel is obtained by freeze drying.
[0016] Furthermore, the preparation method of hydroxyapatite is as follows: hydroxyapatite is prepared by a hydrothermal synthesis method, calcium chloride and sodium phosphate dihydrate are used as calcium source and phosphorus source respectively, and 4 to 10 parts of sodium phosphate dihydrate are gradually added dropwise to 30 to 45 parts of a calcium chloride solution with a concentration of 0.5 mol / L, and stirred for 2 to 4 hours to form a uniform solution, and the solution is subjected to a hydrothermal reaction at 180 to 240° C. for 30 to 40 hours. After the reaction is completed, the product is filtered and washed with deionized water until the pH value of the filtrate is 7, and finally vacuum dried at room temperature.
[0017] The present invention designs a phase-change heat storage aerogel as the heat insulation layer of the heating gloves, which has multiple excellent properties. 1. In terms of phase-change heat storage, the designed phase-change heat storage aerogel uses eicosane as the phase change material. The main reason for choosing eicosane as the heat storage medium is that its phase change temperature is close to body temperature. At the same time, as a high-performance phase-change material, eicosane does not have supercooling and high latent heat. By using its phase change latent heat to store and release heat, it can provide a continuous and stable heat preservation effect during the use of the gloves and extend the heat preservation time. 2. In terms of flexibility, Kevlar fiber aerogel, as the matrix material of the heat insulation layer, has excellent flexibility and tensile strength, can withstand the deformation and stress of the gloves during wearing and use, and ensure the comfort and durability of the gloves. At the same time, the styrene-ethylene-butadiene-styrene block copolymer is composed of hard domains and soft domains, wherein the hard segment is a polystyrene block and the soft segment corresponds to an ethylene / butylene block. The polystyrene blocks are used as cross-linking points, and the ethylene / butylene blocks provide elasticity to form a network structure, giving the thermal insulation layer good compression resilience. After being squeezed and deformed, it can quickly return to its original shape and maintain the shape and thermal insulation performance of the gloves. 3. In terms of thermal insulation, Kevlar fiber aerogel itself has ultra-low thermal conductivity, and its three-dimensional porous network structure can effectively block the conduction and convection of heat. At the same time, the hydroxyapatite coating can improve the reflection and scattering ability of the thermal insulation layer to radiant heat. The synergistic effect of multiple thermal insulation mechanisms enables the phase change thermal storage aerogel to minimize heat loss, provide excellent thermal insulation effects, and ensure the warmth and comfort of the hands. In summary, the phase change thermal storage aerogel designed by the present invention has excellent phase change thermal storage performance, flexibility and thermal insulation performance. It is an excellent thermal insulation layer material for heating gloves, which can significantly improve the user experience and thermal insulation effect of heating gloves.
[0018] The phase change heat storage aerogel designed by the present invention overcomes the limitation that traditional aerogel materials can only be used as heat insulation materials and cannot store heat through phase change. Although traditional aerogel materials have excellent heat insulation performance, they do not have the ability of phase change heat storage. This is because aerogel materials are usually composed of amorphous silicates or carbon-based skeletons, and there is no ordered structure required for crystalline phase change or liquid-solid phase change. The present invention cleverly introduces styrene-ethylene-butadiene-styrene block copolymers into Kevlar fiber aerogels, and realizes heat storage and release through the reversible phase change of the block copolymer, giving the aerogel material a new phase change heat storage function. At the same time, Kevlar fiber aerogel, as a heat insulation matrix, can not only provide excellent heat insulation performance, but also provide a carrier and support for the phase change material to ensure the structural stability of the material during the heat storage process. The organic combination of the two realizes the synergistic improvement of heat insulation and heat storage functions, and develops a new multifunctional aerogel material. Compared with traditional aerogel materials, phase change heat storage aerogel can not only block heat loss, but also actively regulate temperature through the phase change process, showing broad application prospects in the field of thermal insulation.
[0019] Furthermore, the outer layer is made of nylon fabric.
[0020] The present invention selects nylon fabric as the outer material of the gloves, mainly based on the following considerations: nylon has excellent wear resistance, tensile strength and toughness, and can provide good mechanical protection for the gloves, so that they can withstand wear and tear in daily use. At the same time, nylon also has certain waterproof and chemical resistance, which can prevent the infiltration of external moisture and chemicals to a certain extent, and protect the electronic components inside the gloves and the user's hand skin. Taking into account durability, protection and practicality, nylon fabric is an ideal choice as the outer material of the heating gloves, which can meet various needs of the gloves in daily use, extend the service life of the gloves, and improve the user's use experience.
[0021] Furthermore, the heating layer is a graphene-based composite film, and its preparation method is as follows: in parts by weight, 10 to 18 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and 20 to 30 parts of dimethyl sulfoxide are mixed and ultrasonically dispersed for 30 to 45 minutes, and then 2 to 4 parts of graphene are added to continue ultrasonically dispersing the mixed solution in an ice-water mixed bath for 30 to 50 minutes, with an ultrasonic power of 170 to 190 W, and then the ultrasonicated solution is vacuum filtered on a nylon membrane to obtain a film, and then dried in a vacuum oven at 55 to 65° C. for 7 to 12 hours to finally obtain a graphene-based composite film.
[0022] The graphene-based composite film designed by the present invention has the following multiple purposes as the heating layer of the gloves: First, from the perspective of flexibility, the graphene-based composite film exhibits extremely high flexibility and bendability. Graphene, as a two-dimensional nanomaterial, has excellent flexibility and mechanical strength in itself. When it is compounded with materials such as polymers, a composite film with excellent flexibility can be formed. This film can adapt to various deformations such as bending and folding that the gloves may encounter during use, maintaining the integrity of its structure and the stability of its functions. Therefore, as the heating layer of the gloves, the graphene-based composite film can ensure that the gloves always maintain a comfortable fit and flexibility during wearing and use. Secondly, from the perspective of thermoelectric performance, the graphene-based composite film has excellent thermoelectric conversion efficiency and thermal stability. Graphene has extremely high thermal conductivity and electrical conductivity, which means that it can quickly convert electrical energy into thermal energy and effectively transfer heat to the air inside the gloves or the wearer's hands. At the same time, the graphene-based composite film also has good thermal stability and can maintain the stability of its thermoelectric performance over a wide temperature range. This property makes the graphene-based composite film an ideal choice for the heating layer of gloves, which can provide the wearer with lasting warmth and comfort in cold weather. In summary, the graphene-based composite film designed by the present invention as the heating layer of gloves not only has excellent flexibility to adapt to various usage scenarios, but also has excellent thermoelectric properties to ensure efficient heating effect and stable performance. These superior properties make the gloves have significant advantages in warmth, comfort and durability.
[0023] Furthermore, the inner layer is made of bamboo fiber fabric.
[0024] The present invention selects bamboo fiber fabric as the inner layer material of the gloves, mainly because bamboo fiber has natural antibacterial properties, hygroscopicity and air permeability, can effectively inhibit bacterial growth, keep hands fresh and dry, and bamboo fiber also has good flexibility and wear resistance, and is suitable as the inner layer material of the gloves.
[0025] (3) Beneficial technical effects
[0026] 1. The flexible thermally conductive phase change layer designed by the present invention integrates multiple advantages and significantly improves the comprehensive performance of heated gloves. Specifically, PEG10000 is used as a phase change material to efficiently store and regulate heat, effectively avoid overheating and burns, and maintain excellent thermal conductivity at low temperatures. The introduction of tetrabromobisphenol A not only enhances the flame retardant safety of the material, but also gives it a unique self-healing ability and extends its service life. By finely controlling the proportion of raw materials, the mechanical performance is optimized to ensure a balance between tensile strength and elongation at break. In particular, the micro-nano boron nitride filler prepared by an innovative method has a unique microstructure that greatly improves the heat conduction efficiency, bringing the overall thermal conductivity of the flexible thermally conductive phase change layer to a new height.
[0027] 2. The present invention innovatively proposes phase change heat storage aerogel as the thermal insulation layer of heating gloves, integrating multiple advantages: using eicosane as the phase change medium to achieve efficient and stable heat storage and release; using Kevlar fiber aerogel as the matrix, combined with styrene-ethylene-butadiene-styrene block copolymer, giving the material excellent flexibility and compression resilience; combining low thermal conductivity, three-dimensional porous structure and hydroxyapatite coating for radiant heat protection, constructing a multi-level thermal insulation system, significantly reducing heat loss, and providing excellent thermal insulation effects.
[0028] 3. The present invention proposes a thermal insulation glove based on phase change heat storage, which achieves synergistic effect through a carefully designed multi-layer structure. The glove is tightly sewn by an outer layer, a phase change heat storage aerogel, a heating layer, a flexible heat conductive phase change layer and an inner layer, supplemented by a silicone adhesive to enhance the bonding strength between the layers. The outer layer provides basic protection, the phase change heat storage aerogel effectively stores and releases heat, the heating layer provides heat on demand under the control of the temperature control module, the flexible heat conductive phase change layer optimizes heat transfer, and the inner layer ensures a comfortable touch. The power storage bag is made of leather fabric and is equipped with a zipper for easy operation. The built-in rechargeable power supply is connected to the temperature control module to achieve intelligent temperature control. The layers work together to improve the thermal insulation performance and user experience of the gloves. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a front view of a phase-change heat storage and thermal insulation glove proposed by the present invention.
[0030] Figure 2 for Figure 1 Cross-sectional view of the finger at A of the middle glove body.
[0031] Figure 3 This is a transmission electron microscope (TEM) photograph of the leaf-shaped carbon nanotubes of the self-healing flexible carbon-based electrothermal film for gloves prepared in Example 1 of the present invention.
[0032] Figure 4 The self-healing flexible carbon-based electrothermal film for gloves prepared in Example 1 of the present invention is used as a conductor of a light-emitting diode in a series circuit when it is not stretched.
[0033] Figure 5 The self-healing flexible carbon-based electrothermal film of the gloves prepared in Example 1 of the present invention is in a stretched state and serves as a conductor of a light-emitting diode in a series circuit.
[0034] Figure 6 The self-healing flexible carbon-based electrothermal film of the gloves prepared in Example 1 of the present invention is cut and disconnected to serve as a conductor of the light-emitting diode in the series circuit.
[0035] Figure 7The self-healing flexible carbon-based electrothermal film of the gloves prepared in Example 1 of the present invention is used as a conductor of a light-emitting diode in a series circuit after being disconnected and self-healed.
[0036] Explanation of the accompanying drawings: 1. Glove body; 11. Outer layer; 12. Thermal insulation layer; 13. Self-healing flexible carbon-based electric heating film; 14. Flexible carbon-based thermal conductive insulation layer; 15. Inner layer; 2. Elastic band; 3. Power supply bag; 4. Zipper; 6. Temperature control module. DETAILED DESCRIPTION
[0037] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0038] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0039] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies
[0040]
[0041]
[0042] Embodiment 1:
[0043] See also Figure 1-2 , a phase change heat storage and thermal insulation glove, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, a phase change heat storage aerogel 12, a heating layer 13, a flexible heat conductive phase change layer 14 and an inner layer 15 from the outside to the inside; the outer layer 11, the phase change heat storage aerogel 12, the heating layer 13, the flexible heat conductive phase change layer 14 and the inner layer 15 are connected together by stitches and silicone adhesive; a power storage bag 2 is provided at the cuff of the surface of the glove body 1; the power storage bag 2 is made of leather fabric; a zipper 3 is provided on the surface of the power storage bag 2 for easy access; a rechargeable power supply 4 is provided inside the power storage bag 2; a temperature control module 5 is also provided on the back of the glove body 1; the temperature control module 5 is provided with a temperature control button; the rechargeable power supply 4 and the heating layer 13 are respectively connected to the temperature control module 5 through wires.
[0044] The preparation method of the flexible thermal conductive phase change layer 14 is as follows: by weight, 25 parts of PEG 10000, 5 parts of isophorone diisocyanate and 3 parts of micro-nano boron nitride filler are dissolved in 60 parts of chloroform, then heated to 60°C and stirred for 2 hours, then 1 part of tetrabromobisphenol A and 0.3 parts of dibutyltin dilaurate catalyst are added and stirred for 2 hours to obtain a prepolymer mixed solution, then 1 part of triethanolamine and 3 parts of chloroform are mixed, and then the mixed solution is added to the prepolymer mixed solution, stirred for 4 minutes, and then the solution is introduced into a tetrafluoroethylene mold, and then scraped thinly and evenly with a knife, and then the solution in the mold is heated and dried in an oven at 70°C for 10 hours to finally obtain a flexible thermal conductive phase change layer.
[0045] The preparation method of the micro-nano boron nitride filler of the present embodiment is as follows: by weight, 20 parts of a boron nitride whisker preform, 3 parts of a borane ammonia complex, 0.3 parts of ferrocene and 10 parts of dimethylformamide are mixed at room temperature and stirred for 20 minutes, and then dried completely in a vacuum drying oven, and then placed in a tubular furnace at 1000° C. and heat treated for 2 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 5%, and after the reaction is completed, cooled to room temperature to obtain a micro-nano boron nitride filler.
[0046] The preparation method of the boron nitride whisker preform of the present embodiment is as follows: in parts by weight, 4 parts of boric acid, 5 parts of melamine and 100 parts of deionized water are magnetically stirred at 80°C for 30 minutes, and then a white boron nitride precursor is obtained by freeze drying, which is then placed in a tubular furnace at 900°C and heat treated for 3 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 5%, and after the reaction is completed, the preform is cooled to room temperature to obtain a boron nitride whisker preform.
[0047] The micro-nano boron nitride filler of this embodiment is composed of micrometer-scale boron nitride whiskers and nanometer-scale boron nitride nanowires, wherein the boron nitride nanowires are uniformly dispersed on the surface of the boron nitride whiskers in a radial form.
[0048] The preparation method of the phase change heat storage aerogel 12 is as follows: in parts by weight, 3 parts of styrene-ethylene-butadiene-styrene block copolymer, 10 parts of eicosane, and 30 parts of tetrahydrofuran are stirred at room temperature for 2 hours, and then 20 parts of Kevlar fiber aerogel are completely impregnated therein, and then dried in a vacuum drying oven at room temperature for 24 hours to obtain the phase change heat storage aerogel.
[0049] The preparation method of the Kevlar fiber aerogel of this embodiment is as follows: by weight, 5 parts of hydroxyapatite and 45 parts of dimethyl sulfoxide are mixed evenly to obtain a solution A for use; 20 parts of Kevlar fiber and 20 parts of potassium hydroxide are mixed evenly, and then added to 120 parts of dimethyl sulfoxide, mixed and stirred for 48 hours to obtain a reddish brown colloid; then, the solution A is added to the reddish brown colloid, and the stirring is continued for 10 hours, and then the Kevlar fiber aerogel is obtained by freeze drying.
[0050] The preparation method of hydroxyapatite in this embodiment is as follows: hydroxyapatite is prepared by a hydrothermal synthesis method, calcium chloride and sodium phosphate dihydrate are used as calcium source and phosphorus source respectively, 4 parts of sodium phosphate dihydrate are gradually added dropwise to 30 parts of 0.5 mol / L calcium chloride solution in parts by weight, and stirred for 2 hours to form a uniform solution, and the solution is subjected to a hydrothermal reaction at 180° C. for 30 hours. After the reaction is completed, the product is filtered and washed with deionized water until the pH value of the filtrate is 7, and finally vacuum dried at room temperature.
[0051] The outer layer 11 is made of nylon fabric.
[0052] The heating layer 14 is a graphene-based composite film, and its preparation method is as follows: in parts by weight, 10 parts of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) and 20 parts of dimethyl sulfoxide are mixed and ultrasonically dispersed for 30 minutes, and then 2 parts of graphene are added to continue ultrasonically dispersing the mixed solution in an ice-water mixed bath for 30 minutes, with an ultrasonic power of 170 W, and then the ultrasonicated solution is vacuum filtered on a nylon membrane to obtain a film, and then dried in a vacuum oven at 55°C for 7 hours to finally obtain a graphene-based composite film.
[0053] The inner layer 15 is made of bamboo fiber fabric.
[0054] Example 2
[0055] See also Figure 1-2 , a phase change heat storage and thermal insulation glove, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, a phase change heat storage aerogel 12, a heating layer 13, a flexible heat conductive phase change layer 14 and an inner layer 15 from the outside to the inside; the outer layer 11, the phase change heat storage aerogel 12, the heating layer 13, the flexible heat conductive phase change layer 14 and the inner layer 15 are connected together by stitches and silicone adhesive; a power storage bag 2 is provided at the cuff of the surface of the glove body 1; the power storage bag 2 is made of leather fabric; a zipper 3 is provided on the surface of the power storage bag 2 for easy access; a rechargeable power supply 4 is provided inside the power storage bag 2; a temperature control module 5 is also provided on the back of the glove body 1; the temperature control module 5 is provided with a temperature control button; the rechargeable power supply 4 and the heating layer 13 are respectively connected to the temperature control module 5 through wires.
[0056] The preparation method of the flexible thermal conductive phase change layer 14 is as follows: by weight, 32 parts of PEG 10000, 7 parts of isophorone diisocyanate and 5 parts of micro-nano boron nitride filler are dissolved in 72 parts of chloroform, then heated to 64°C and stirred for 3 hours, then 2 parts of tetrabromobisphenol A and 0.5 parts of dibutyltin dilaurate catalyst are added and stirred for 3 hours to obtain a prepolymer mixed solution, then 2 parts of triethanolamine and 5 parts of chloroform are mixed, and then the mixed solution is added to the prepolymer mixed solution, and after stirring for 7 minutes, the solution is introduced into a tetrafluoroethylene mold, and then scraped thinly and evenly with a knife, and then the solution in the mold is heated and dried in an oven at 76°C for 14 hours to finally obtain a flexible thermal conductive phase change layer.
[0057] The preparation method of the micro-nano boron nitride filler of the present embodiment is as follows: by weight, 26 parts of a boron nitride whisker preform, 4 parts of a borane-amine complex, 0.5 parts of ferrocene and 14 parts of dimethylformamide are mixed at room temperature and stirred for 22 minutes, and then dried completely in a vacuum drying oven, and then placed in a tubular furnace at 1100° C. and heat treated for 3 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 7%, and after the reaction is completed, cooled to room temperature to obtain a micro-nano boron nitride filler.
[0058] The preparation method of the boron nitride whisker preform of the present embodiment is as follows: by weight, 6 parts of boric acid, 8 parts of melamine and 100 parts of deionized water are magnetically stirred at 86° C. for 45 minutes, and then a white boron nitride precursor is obtained by freeze drying. The precursor is then placed in a tubular furnace at 1000° C. and heat treated for 4 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 7%. After the reaction is completed, the precursor is cooled to room temperature to obtain a boron nitride whisker preform.
[0059] The micro-nano boron nitride filler of this embodiment is composed of micrometer-scale boron nitride whiskers and nanometer-scale boron nitride nanowires, wherein the boron nitride nanowires are uniformly dispersed on the surface of the boron nitride whiskers in a radial form.
[0060] The preparation method of the phase change heat storage aerogel 12 is as follows: in parts by weight, 5 parts of styrene-ethylene-butadiene-styrene block copolymer, 13 parts of eicosane, and 37 parts of tetrahydrofuran are stirred at room temperature for 4 hours, and then 26 parts of Kevlar fiber aerogel are completely impregnated therein, and then dried in a vacuum drying oven at room temperature for 30 hours to obtain the phase change heat storage aerogel.
[0061] The preparation method of the Kevlar fiber aerogel of this embodiment is as follows: by weight, 7 parts of hydroxyapatite and 57 parts of dimethyl sulfoxide are mixed evenly to obtain a solution A for use; 26 parts of Kevlar fiber and 26 parts of potassium hydroxide are mixed evenly, and then added to 138 parts of dimethyl sulfoxide, mixed and stirred for 51 hours to obtain a reddish brown colloid; then, the solution A is added to the reddish brown colloid, and the stirring is continued for 15 hours, and then the Kevlar fiber aerogel is obtained by freeze drying.
[0062] The preparation method of hydroxyapatite in this embodiment is as follows: hydroxyapatite is prepared by a hydrothermal synthesis method, calcium chloride and sodium phosphate dihydrate are used as calcium source and phosphorus source respectively, and 7 parts of sodium phosphate dihydrate are gradually added dropwise to 36 parts of calcium chloride solution with a concentration of 0.5 mol / L, and stirred for 3 hours to form a uniform solution, and the solution is subjected to a hydrothermal reaction at 210° C. for 35 hours. After the reaction is completed, the product is filtered and washed with deionized water until the pH value of the filtrate is 7, and finally vacuum dried at room temperature.
[0063] The outer layer 11 is made of nylon fabric.
[0064] The heating layer 14 is a graphene-based composite film, and its preparation method is as follows: in parts by weight, 14 parts of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) and 25 parts of dimethyl sulfoxide are mixed and ultrasonically dispersed for 38 minutes, and then 3 parts of graphene are added to continue ultrasonically dispersing the mixed solution in an ice-water mixed bath for 40 minutes, with an ultrasonic power of 180 W, and then the ultrasonicated solution is vacuum filtered on a nylon membrane to obtain a film, and then dried in a vacuum oven at 60°C for 10 hours to finally obtain a graphene-based composite film.
[0065] The inner layer 15 is made of bamboo fiber fabric.
[0066] Example 3
[0067] See also Figure 1-2 , a phase change heat storage and thermal insulation glove, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, a phase change heat storage aerogel 12, a heating layer 13, a flexible heat conductive phase change layer 14 and an inner layer 15 from the outside to the inside; the outer layer 11, the phase change heat storage aerogel 12, the heating layer 13, the flexible heat conductive phase change layer 14 and the inner layer 15 are connected together by stitches and silicone adhesive; a power storage bag 2 is provided at the cuff of the surface of the glove body 1; the power storage bag 2 is made of leather fabric; a zipper 3 is provided on the surface of the power storage bag 2 for easy access; a rechargeable power supply 4 is provided inside the power storage bag 2; a temperature control module 5 is also provided on the back of the glove body 1; the temperature control module 5 is provided with a temperature control button; the rechargeable power supply 4 and the heating layer 13 are respectively connected to the temperature control module 5 through wires.
[0068] The preparation method of the flexible thermally conductive phase change layer 14 is as follows: by weight, 34 parts of PEG 10000, 9 parts of isophorone diisocyanate and 6 parts of micro-nano boron nitride filler are dissolved in 78 parts of chloroform, then heated to 64°C and stirred for 3 hours, then 3 parts of tetrabromobisphenol A and 0.6 parts of dibutyltin dilaurate catalyst are added and stirred for 3 hours to obtain a prepolymer mixed solution, then 2 parts of triethanolamine and 6 parts of chloroform are mixed, and then the mixed solution is added to the prepolymer mixed solution, and after stirring for 7 minutes, the solution is introduced into a tetrafluoroethylene mold, and then scraped thinly and evenly with a knife, and then the solution in the mold is heated and dried in an oven at 79°C for 14 hours to finally obtain a flexible thermally conductive phase change layer.
[0069] The preparation method of the micro-nano boron nitride filler of the present embodiment is as follows: by weight, 29 parts of a boron nitride whisker preform, 5 parts of a borane ammonia complex, 0.6 parts of ferrocene and 14 parts of dimethylformamide are mixed at room temperature and stirred for 23 minutes, and then dried completely in a vacuum drying oven, and then placed in a tubular furnace at 1120° C. and heat treated for 3 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 8%, and after the reaction is completed, cooled to room temperature to obtain a micro-nano boron nitride filler.
[0070] The preparation method of the boron nitride whisker preform of the present embodiment is as follows: by weight, 7 parts of boric acid, 9 parts of melamine and 100 parts of deionized water are magnetically stirred at 87° C. for 45 minutes, and then a white boron nitride precursor is obtained by freeze drying. The precursor is then placed in a tubular furnace at 1020° C. and heat treated for 5 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 8%. After the reaction is completed, the precursor is cooled to room temperature to obtain a boron nitride whisker preform.
[0071] The micro-nano boron nitride filler of this embodiment is composed of micrometer-scale boron nitride whiskers and nanometer-scale boron nitride nanowires, wherein the boron nitride nanowires are uniformly dispersed on the surface of the boron nitride whiskers in a radial form.
[0072] The preparation method of the phase change heat storage aerogel 12 is as follows: in parts by weight, 6 parts of styrene-ethylene-butadiene-styrene block copolymer, 14 parts of eicosane, and 40 parts of tetrahydrofuran are stirred at room temperature for 4 hours, and then 31 parts of Kevlar fiber aerogel are completely impregnated therein, and then dried in a vacuum drying oven at room temperature for 30 hours to obtain the phase change heat storage aerogel.
[0073] The preparation method of the Kevlar fiber aerogel of this embodiment is as follows: by weight, 8 parts of hydroxyapatite and 59 parts of dimethyl sulfoxide are mixed evenly to obtain a solution A for use; 29 parts of Kevlar fiber and 29 parts of potassium hydroxide are mixed evenly, and then added to 137 parts of dimethyl sulfoxide, mixed and stirred for 51 hours to obtain a reddish brown colloid; then, the solution A is added to the reddish brown colloid, and the stirring is continued for 15 hours, and then the Kevlar fiber aerogel is obtained by freeze drying.
[0074] The preparation method of hydroxyapatite in this embodiment is as follows: hydroxyapatite is prepared by a hydrothermal synthesis method, calcium chloride and sodium phosphate dihydrate are used as calcium source and phosphorus source respectively, 7 parts of sodium phosphate dihydrate are gradually added dropwise to 38 parts of 0.5 mol / L calcium chloride solution, and stirred for 3 hours to form a uniform solution, and the solution is subjected to a hydrothermal reaction at 215° C. for 35 hours. After the reaction is completed, the product is filtered and washed with deionized water until the pH value of the filtrate is 7, and finally vacuum dried at room temperature.
[0075] The outer layer 11 is made of nylon fabric.
[0076] The heating layer 14 is a graphene-based composite film, and its preparation method is as follows: in parts by weight, 13 parts of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) and 26 parts of dimethyl sulfoxide are mixed and ultrasonically dispersed for 38 minutes, and then 3 parts of graphene are added to continue ultrasonically dispersing the mixed solution in an ice-water mixed bath for 41 minutes, with an ultrasonic power of 180 W, and then the ultrasonicated solution is vacuum filtered on a nylon membrane to obtain a film, and then dried in a vacuum oven at 60°C for 9 hours to finally obtain a graphene-based composite film.
[0077] The inner layer 15 is made of bamboo fiber fabric.
[0078] Example 4
[0079] See also Figure 1-2 , a phase change heat storage and thermal insulation glove, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, a phase change heat storage aerogel 12, a heating layer 13, a flexible heat conductive phase change layer 14 and an inner layer 15 from the outside to the inside; the outer layer 11, the phase change heat storage aerogel 12, the heating layer 13, the flexible heat conductive phase change layer 14 and the inner layer 15 are connected together by stitches and silicone adhesive; a power storage bag 2 is provided at the cuff of the surface of the glove body 1; the power storage bag 2 is made of leather fabric; a zipper 3 is provided on the surface of the power storage bag 2 for easy access; a rechargeable power supply 4 is provided inside the power storage bag 2; a temperature control module 5 is also provided on the back of the glove body 1; the temperature control module 5 is provided with a temperature control button; the rechargeable power supply 4 and the heating layer 13 are respectively connected to the temperature control module 5 through wires.
[0080] The preparation method of the flexible thermally conductive phase change layer 14 is as follows: by weight, 45 parts of PEG 10000, 12 parts of isophorone diisocyanate and 8 parts of micro-nano boron nitride filler are dissolved in 90 parts of chloroform, then heated to 70°C and stirred for 4 hours, then 4 parts of tetrabromobisphenol A and 0.8 parts of dibutyltin dilaurate catalyst are added and stirred for 4 hours to obtain a prepolymer mixed solution, then 3 parts of triethanolamine and 8 parts of chloroform are mixed, and then the mixed solution is added to the prepolymer mixed solution, and after stirring for 10 minutes, the solution is introduced into a tetrafluoroethylene mold, and then scraped thinly and evenly with a knife, and then the solution in the mold is heated and dried in an oven at 85°C for 18 hours to finally obtain the flexible thermally conductive phase change layer 14.
[0081] The preparation method of the micro-nano boron nitride filler of the present embodiment is as follows: by weight, 35 parts of a boron nitride whisker preform, 6 parts of a borane ammonia complex, 0.8 parts of ferrocene and 18 parts of dimethylformamide are mixed at room temperature and stirred for 25 minutes, and then dried completely in a vacuum drying oven, and then placed in a tubular furnace at 1200° C. and heat treated for 4 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 10%, and after the reaction is completed, cooled to room temperature to obtain a micro-nano boron nitride filler.
[0082] The preparation method of the boron nitride whisker preform of the present embodiment is as follows: in parts by weight, 10 parts of boric acid, 12 parts of melamine and 100 parts of deionized water are magnetically stirred at 95° C. for 60 minutes, and then a white boron nitride precursor is obtained by freeze drying. The precursor is then placed in a tubular furnace at 1100° C. and heat treated for 6 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 10%. After the reaction is completed, the precursor is cooled to room temperature to obtain a boron nitride whisker preform.
[0083] The micro-nano boron nitride filler of this embodiment is composed of micrometer-scale boron nitride whiskers and nanometer-scale boron nitride nanowires, wherein the boron nitride nanowires are uniformly dispersed on the surface of the boron nitride whiskers in a radial form.
[0084] The preparation method of the phase change heat storage aerogel 12 is as follows: by weight, 7 parts of styrene-ethylene-butadiene-styrene block copolymer, 16 parts of eicosane, and 45 parts of tetrahydrofuran are stirred at room temperature for 5 hours, and then 35 parts of Kevlar fiber aerogel are completely impregnated therein, and then dried in a vacuum drying oven at room temperature for 36 hours to obtain the phase change heat storage aerogel 12.
[0085] The preparation method of the Kevlar fiber aerogel of this embodiment is as follows: by weight, 10 parts of hydroxyapatite and 70 parts of dimethyl sulfoxide are mixed evenly to obtain a solution A for use; 35 parts of Kevlar fiber and 35 parts of potassium hydroxide are mixed evenly, and then added to 155 parts of dimethyl sulfoxide, mixed and stirred for 54 hours to obtain a reddish brown colloid; then, the solution A is added to the reddish brown colloid, and the stirring is continued for 20 hours, and then the Kevlar fiber aerogel is obtained by freeze drying.
[0086] The preparation method of hydroxyapatite in this embodiment is as follows: hydroxyapatite is prepared by a hydrothermal synthesis method, calcium chloride and sodium phosphate dihydrate are used as calcium source and phosphorus source respectively, and 10 parts of sodium phosphate dihydrate are gradually added dropwise to 45 parts of 0.5 mol / L calcium chloride solution in parts by weight, and stirred for 4 hours to form a uniform solution, and the solution is subjected to a hydrothermal reaction at 240° C. for 40 hours. After the reaction is completed, the product is filtered and washed with deionized water until the pH value of the filtrate is 7, and finally vacuum dried at room temperature.
[0087] The outer layer 11 is made of nylon fabric.
[0088] The heating layer 14 is a graphene-based composite film, and its preparation method is as follows: in parts by weight, 18 parts of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) and 30 parts of dimethyl sulfoxide are mixed and ultrasonically dispersed for 45 minutes, and then 4 parts of graphene are added to continue ultrasonically dispersing the mixed solution in an ice-water mixed bath for 50 minutes, with an ultrasonic power of 190 W, and then the ultrasonicated solution is vacuum filtered on a nylon membrane to obtain a film, and then dried in a vacuum oven at 65°C for 12 hours to finally obtain a graphene-based composite film.
[0089] The inner layer 15 is made of bamboo fiber fabric.
[0090] Example 5
[0091] It is basically the same as Example 1, except that the self-healing flexible carbon-based electric heating film 13 contains 7 parts of leaf-shaped carbon nanotubes.
[0092] Comparative Example 1
[0093] It is basically the same as Example 1, except that original multi-walled carbon nanotubes are added to prepare the self-healing flexible carbon-based electric heating film instead of leaf-shaped carbon nanotubes.
[0094] Comparative Example 2
[0095] It is basically the same as Example 1, except that no borax decahydrate is added in the preparation of the self-healing flexible carbon-based electric heating film.
[0096] Characterization Tests:
[0097] Figure 3Transmission electron microscope photos show the structure of leaf-shaped carbon nanotubes in the self-healing flexible carbon-based electrothermal film of the gloves in Example 1 of the present invention. The darker ones are similar to petioles, and the lighter ones are similar to leaves, confirming its successful preparation.
[0098] Figure 4 The self-healing flexible carbon-based electrothermal film of the gloves prepared in Example 1 of the present invention is used as a conductor of a light-emitting diode in a series circuit when it is not stretched. Figure 5 The self-healing flexible carbon-based electrothermal film of the glove prepared in Example 1 of the present invention is in a stretched state and is used as a conductor of a light-emitting diode in a series circuit. After rigorous experimental testing of the self-healing flexible carbon-based electrothermal film prepared in Example 1 of the present invention, the film's ability to serve as a conductive medium for the light-emitting diode in the series circuit is not affected after undergoing stretching deformation, and it can still ensure the effective transmission of current, thereby driving the diode to emit light normally. This experimental result conclusively proves that the film has excellent conductivity stability under normal strain (especially in the stretched state), and its electrothermal function is maintained. Figure 4 and Figure 5 The comparative analysis further strengthened this discovery, revealing the robustness of the conductive network of the film during deformation and the persistence of its electrothermal effect, providing important experimental basis and theoretical support for the research of thermoelectric films for wearable heating gloves.
[0099] like Figure 6 As shown in Figure 1, when the film was cut off when it was used as a conductor of a light-emitting diode in a series circuit, the circuit was immediately interrupted and the diode stopped emitting light, which verified the impact of the destruction of the circuit integrity on the conductive properties. However, after the film was kept in a moisturizing state for 24 hours after contact, self-healing occurred (as shown in Figure 1). Figure 7 As shown in the figure, the film successfully healed itself and was connected to the circuit as a wire again, making the diode emit light again. This remarkable phenomenon not only directly proves that the film has the ability to self-repair fractures and restore its conductive function, but also reflects its high reliability in autonomously restoring integrity and performance after damage. Therefore, the conclusions of this study strongly support the potential value of self-healing flexible carbon-based electrothermal films in glove applications that require high durability and easy maintenance.
[0100] Performance Testing:
[0101] Mechanical properties test: The mechanical properties test of the self-healing flexible carbon-based electric heating film was conducted using a microcomputer-controlled universal material testing machine (SANS-CMT4204) at a preset tensile rate of 2 mm / min. During the test, the film sample was precisely installed between the fixtures of the testing machine to ensure the consistency of the test environment. The tensile strength and elongation at break of the film were evaluated through the automatically recorded stress-strain curve. These parameters directly reflect the strength and flexibility of the film when subjected to tension.
[0102] Electrothermal performance: The electrothermal performance test of the self-healing flexible carbon-based electrothermal film adopts a professional thermoelectric parameter test system (ADVANCE RIKO Inc., Japan). The system can accurately measure the conductivity and Seebeck coefficient of the film, so as to comprehensively evaluate its electrothermal conversion efficiency and thermoelectric properties. During the test, the film sample is placed in a standard test environment to ensure the consistency of the test conditions. A stable current or temperature gradient is applied by the system, and the voltage change or temperature difference across the film is measured to calculate the conductivity and Seebeck coefficient. These parameters directly reflect the conductive properties and thermoelectric conversion capabilities of the film, and provide important performance indicators and scientific basis for the application of self-healing flexible carbon-based electrothermal films in heating, temperature control and energy conversion.
[0103] Self-healing ability: In order to evaluate the self-healing ability of the self-healing flexible carbon-based electric heating film, we performed the following test process: First, use a sharp blade to accurately cut the film sample; then, use a special clamp to clamp the cut ends tightly together to ensure that they maintain a stable contact state; then, place this combination in a humid environment for 24 hours to simulate and promote the self-healing process; finally, the film sample is tested for thermoelectric performance again, focusing on key indicators such as its conductivity and Seebeck coefficient, so as to comprehensively evaluate the degree of recovery of its self-healing ability to electric and thermal performance. At the same time, the same method is used to test the mechanical properties after self-healing, focusing on evaluating its tensile strength and elongation.
[0104] The properties of the self-healing flexible carbon-based electric heating films of Examples 1 to 5 and Comparative Examples 1 to 2 are summarized in Table 2.
[0105] Table 2 Performance summary of self-healing flexible carbon-based electric heating films of Examples 1 to 5 and Comparative Examples 1 to 2
[0106]
[0107] The main difference between Comparative Example 1 and Example 1 is whether the carbon nanotubes are original multi-walled carbon nanotubes or leaf-shaped carbon nanotubes. As can be seen from Table 2, the use of leaf-shaped carbon nanotubes significantly increases the tensile strength and electrothermal performance of the self-healing flexible carbon-based electrothermal film. This is because the design of leaf-shaped carbon nanotubes achieves multiple advantages: its unique overall structural design is conducive to the smooth conduction of electrons and phonons inside the material, thereby greatly improving the thermal and electrical conductivity of the material; at the same time, the multi-level structure significantly increases the specific surface area of the material, provides more contact area, is conducive to the uniform dispersion and effective transmission of external forces and stresses inside the material, and enhances the mechanical properties of the material; in addition, the leaf part can produce deformation, absorb and buffer impact energy, and the petiole part plays a stable support and load transfer role, which together improves the comprehensive performance of the material, including good elasticity and impact resistance. These advantages make leaf-shaped carbon nanotubes perform better than original multi-walled carbon nanotubes in self-healing flexible carbon-based electrothermal films.
[0108] The main difference between Comparative Example 2 and Example 1 is whether borax decahydrate is added to the self-healing flexible carbon-based electric heating film. As can be seen from Table 2, the addition of borax decahydrate can significantly improve the self-healing ability of the self-healing flexible carbon-based electric heating film. This is because borax decahydrate plays a key role as a cross-linking agent in the film, undergoes a cross-linking reaction with the hydroxyl groups on the polyvinyl alcohol molecular chain, and forms a stable cross-linked structure. When the film is damaged by the outside world, this cross-linked structure can respond quickly, and promote the self-repair of the damaged area through rearrangement and cross-linking between molecules. Specifically, the addition of borax decahydrate enhances the interaction force between the polyvinyl alcohol molecular chains, so that when the film is damaged, it can use these interaction forces to rearrange the molecular chains and fill the damaged area, thereby achieving self-repair. In addition, by adjusting the content of borax decahydrate, the speed and effect of self-repair can be finely controlled to meet the needs of different application scenarios. Therefore, adding borax decahydrate is an effective means to enhance the self-healing ability of the self-healing flexible carbon-based electric heating film.
[0109] In summary, the electric heating gloves of the present invention use a self-healing flexible carbon-based electric heating film as the core, which combines the excellent conductivity of graphene and the excellent thermal conductivity of carbon nanotubes, not only achieving a double leap in electric heat conversion efficiency and thermal conductivity, but also significantly improving the durability and reliability of the gloves through the self-healing mechanism. The self-healing ability means that the gloves can automatically repair themselves when they suffer minor damage, reducing performance degradation or failure caused by damage, thereby extending the service life and reducing maintenance costs.
[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A heat storage and thermal insulation glove based on phase change, characterized in that: The glove body (1) comprises an outer layer (11), a phase change heat storage aerogel (12), a heating layer (13), a flexible heat conductive phase change layer (14) and an inner layer (15) from the outside to the inside; the outer layer (11), the phase change heat storage aerogel (12), the heating layer (13), the flexible heat conductive phase change layer (14) and the inner layer (15) are connected together by stitches and a silicone adhesive; a power storage bag (2) is provided at the cuff of the surface of the glove body (1); the power storage bag (2) is made of leather; a zipper (3) is provided on the surface of the power storage bag (2) for easy access; a rechargeable power supply (4) is provided inside the power storage bag (2); a temperature control module (5) is also provided on the back of the glove body (1); the temperature control module (5) is provided with a temperature control button; the rechargeable power supply (4) and the heating layer (13) are respectively connected to the temperature control module (5) by wires; The preparation method of the flexible thermal conductive phase change layer (14) is as follows: by weight, 25 to 45 parts of PEG 10000, 5 to 12 parts of isophorone diisocyanate and 3 to 8 parts of micro-nano boron nitride filler are dissolved in 60 to 90 parts of chloroform, then heated to 60 to 70°C and stirred for 2 to 4 hours, then 1 to 4 parts of tetrabromobisphenol A and 0.3 to 0.8 parts of dibutyltin dilaurate catalyst are added and stirred for 2 to 4 hours to obtain a prepolymer mixed solution, then 1 to 3 parts of triethanolamine and 3 to 8 parts of chloroform are mixed, and then the mixed solution is added to the prepolymer mixed solution, stirred for 4 to 10 minutes, and then the solution is poured into a tetrafluoroethylene mold, and then scraped thinly and evenly with a knife, and then the solution in the mold is heated and dried in an oven at 70 to 85°C for 10 to 18 hours, and finally a flexible thermal conductive phase change layer is obtained; The preparation method of the phase change heat storage aerogel (12) is as follows: by weight, 3 to 7 parts of styrene-ethylene-butadiene-styrene block copolymer, 10 to 16 parts of eicosane, and 30 to 45 parts of tetrahydrofuran are stirred at room temperature for 2 to 5 hours, and then 20 to 35 parts of Kevlar fiber aerogel are completely impregnated therein, and then dried in a vacuum drying oven at room temperature for 24 to 36 hours to obtain the phase change heat storage aerogel.
2. The heat storage gloves based on phase change as claimed in claim 1, characterized in that: The preparation method of the micro-nano boron nitride filler is as follows: by weight, 20 to 35 parts of a boron nitride whisker preform, 3 to 6 parts of a borane ammonia complex, 0.3 to 0.8 parts of ferrocene and 10 to 18 parts of dimethylformamide are mixed at room temperature and stirred for 20 to 25 minutes, and then completely dried in a vacuum drying oven, and then placed in a tubular furnace at 1000 to 1200° C., and heat treated for 2 to 4 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 5 to 10%, and after the reaction is completed, cooled to room temperature to obtain the micro-nano boron nitride filler.
3. The heat storage gloves based on phase change as claimed in claim 2, characterized in that: The preparation method of the boron nitride whisker preform is as follows: by weight, 4 to 10 parts of boric acid, 5 to 12 parts of melamine and 100 parts of deionized water are magnetically stirred at 80 to 95° C. for 30 to 60 minutes, then a white boron nitride precursor is obtained by freeze drying, and then the precursor is placed in a tubular furnace at 900 to 1100° C., and heat-treated for 3 to 6 hours in a mixed atmosphere of nitrogen and hydrogen, wherein the volume percentage of hydrogen is 5 to 10%, and after the reaction is completed, the precursor is cooled to room temperature to obtain a boron nitride whisker preform.
4. A phase-change heat storage and thermal insulation glove as claimed in claim 2 or 3, characterized in that: The micro-nano boron nitride filler is composed of micrometer-scale boron nitride whiskers and nanometer-scale boron nitride nanowires, wherein the boron nitride nanowires are uniformly dispersed on the surface of the boron nitride whiskers in a radial form.
5. The heat storage gloves based on phase change as claimed in claim 1, characterized in that: The preparation method of the Kevlar fiber aerogel is as follows: by weight, 5 to 10 parts of hydroxyapatite and 45 to 70 parts of dimethyl sulfoxide are mixed evenly to obtain a solution A for standby use; 20 to 35 parts of Kevlar fiber and 20 to 35 parts of potassium hydroxide are mixed evenly, and then added into 120 to 155 parts of dimethyl sulfoxide, mixed and stirred for 48 to 54 hours to obtain a reddish brown colloid; then, the solution A is added into the reddish brown colloid, and stirring is continued for 10 to 20 hours, and then the Kevlar fiber aerogel is obtained by freeze drying.
6. The heat storage gloves based on phase change as claimed in claim 5, characterized in that: The preparation method of hydroxyapatite is as follows: hydroxyapatite is prepared by a hydrothermal synthesis method, calcium chloride and sodium phosphate dihydrate are used as calcium source and phosphorus source respectively, 4 to 10 parts of sodium phosphate dihydrate are gradually added dropwise to 30 to 45 parts of a calcium chloride solution with a concentration of 0.5 mol / L, stirred for 2 to 4 hours to form a uniform solution, the solution is subjected to a hydrothermal reaction at 180 to 240° C. for 30 to 40 hours, the product is filtered after the reaction is completed, and washed with deionized water until the pH value of the filtrate is 7, and finally vacuum dried at room temperature.
7. The heat storage gloves based on phase change as claimed in claim 1, characterized in that: The outer layer (11) is made of nylon fabric; the inner layer (15) is made of bamboo fiber fabric.
8. The heat storage gloves based on phase change as claimed in claim 1, characterized in that: The heating layer (13) is a graphene-based composite film, and its preparation method is as follows: by weight, 10 to 18 parts of poly (3, 4-ethylenedioxythiophene) - poly (styrene sulfonic acid) and 20 to 30 parts of dimethyl sulfoxide are mixed and ultrasonically dispersed for 30 to 45 minutes, and then 2 to 4 parts of graphene are added to continue ultrasonically dispersing the mixed solution in an ice-water mixed bath for 30 to 50 minutes, with an ultrasonic power of 170 to 190 W, and then the ultrasonicated solution is filtered by vacuum on a nylon membrane to obtain a film, and then dried in a vacuum oven at 55 to 65° C. for 7 to 12 hours, and finally the graphene-based composite film is obtained.
Citation Information
Patent Citations
Phase change material thermal insulation gloves
CN202873889U
Temperature sensing protective gloves
CN206260906U
Flexible boron nitride nano-belt aerogel and preparation method therefor
CN109704296A
Preparation method of graphene and boron nitride composite material
CN112588259A